2018
DOI: 10.1259/bjrcr.20170114
|View full text |Cite
|
Sign up to set email alerts
|

A rare suspected case of chronic nodular granulomatous herpes simplex encephalitis in an adult

Abstract: Herpes simplex encephalitis is the most common sporadic viral encephalitis in the western world, HSV-1 (herpes simplex virus) being the mostly commonly implicated serotype. The disease is usually monophasic, although patients may relapse weeks, months or years after initial infection. This chronic granulomatous inflammatory process is almost exclusively described in children and rarely forms discrete enhancing parenchymal nodules. We present the clinical and radiological features of an unusual case of chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Rare cases of histologically confirmed chronic granulomatous herpes encephalitis occurring in adults have been reported. 10 Subacute HSVE is rarely described in the literature being reported 4 times only (Table 1), and it was biphasic in 2 of them (our literature review was concluded on March 9, 2020). First case was by Hlavka et al, 11 as 58 years old woman with a biphasic course that lasted for 3 months.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Rare cases of histologically confirmed chronic granulomatous herpes encephalitis occurring in adults have been reported. 10 Subacute HSVE is rarely described in the literature being reported 4 times only (Table 1), and it was biphasic in 2 of them (our literature review was concluded on March 9, 2020). First case was by Hlavka et al, 11 as 58 years old woman with a biphasic course that lasted for 3 months.…”
Section: Discussionmentioning
confidence: 93%
“…Schutz et al9 noted that all published cases of biphasic chronic granulomatous HSVE were documented to have occurred in children. Rare cases of histologically confirmed chronic granulomatous herpes encephalitis occurring in adults have been reported 10…”
Section: Discussionmentioning
confidence: 99%